Effect of early intervention in infants at very high risk of cerebral palsy: a systematic review. (7th December 2016) - Hadders‐Algra, Mijna; Boxum, Anke G; Hielkema, Tjitske; Hamer, Elisa G
Abstract : Aim: First, to systematically review the evidence on the effect of intervention applied during the first postnatal year in infants with or at very high risk of cerebral palsy (CP) on child and family outcome. Second, to assess whether type and dosing of intervention modify the effect of intervention. Method: Relevant literature was identified by searching the PubMed, Embase, and CINAHL databases. Selection criteria included infants younger than 12 months corrected age with or at very high risk of CP. Methodological quality including risk of bias was scrutinized. Results: Thirteen papers met the inclusion criteria. Seven studies with moderate to high methodological quality were analysed in detail; they evaluated neurodevelopmental treatment only ( n =2), multisensory stimulation ( n =1), developmental stimulation ( n =2), and multifaceted interventions consisting of a mix of developmental stimulation, support of parent–infant interaction, and neurodevelopmental treatment ( n =2). The heterogeneity precluded conclusions. Yet, two suggestions emerged: (1) dosing may be critical for effectiveness; (2) multifaceted intervention may offer best opportunities for child and family. Interpretation: The literature on early intervention in very high‐risk infants with sufficient methodological quality is limited, heterogeneous, and provides weak evidence on the effect. More studies are urgently needed. Suggestions for future research are provided. What this paper adds: Evidence of effect of early intervention during the first postnatal year in infants at very high risk of cerebral palsy is weak. Suggests dosing may be critical in the effectiveness of early intervention. Suggests multifaceted intervention may be more effective than single component intervention.